Aktivitas urikase yang dihasilkan dari berbagai sel lactobacillus plantarum dan parameter kinetikanya - Dyah Iswantini; Novik Nurhidayat; . Trivadila; Eka Mardiah (Jurnal Ilmu Pertanian Indonesia, 2009)
Uric acid concentration could be determined by spectrophotometry method. Uric acid was oxidized into allatonin in the presence of uricase and calculated by measuring the decrease of uric acid absorbance at 293 nm. These uricase were obtained from cells of Lactobacillus plantarum. L. plantarum K. Mar. E was isolated from passion fruit skin and L. plantarum Mgs. Psmb and Mgs. Bst from mangosteen. This research was conducted to observe the activity and kinetics of uricase from various cells of L. plantarum by spectrophotometric method. The plate assay method indicated that L. plantarum produced uricase, based on the clear zone about 0,2 mm on glucose yeast peptone medium contained 0,2% uric acid. The optimum condition of uricase activity from the three different sources occured in physiological condition. Uricase activity generated from cells of L. p/antarum K. Mar. E, Mgs. Psmb, and Mgs. Bst were 0,1073; 0,0867; and 0,0842 U/ml, respectively. The kinetic parameters for uricase, determined with uric acid as the substrate. Vmax produced by L. plantarum K. Mar. E, Mgs. Psmb, and Mgs. Bst were 1,3635; 0,0316; and 0,0418 U/ml of bacterial culture, respectively and KM 0,1541; 0,0061; and0,0054 mM, respectively. Uricase activity in various bacterial cells of L. plantarum was stable until the second day.